2015
DOI: 10.1186/s13104-015-1319-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype correlations in Iranian patients with hyperinsulinaemic hypoglycaemia

Abstract: BackgroundHyperinsulinaemic hypoglycaemia (HH) is a group of clinically and genetically heterogeneous disorders characterized by unregulated insulin secretion. Abnormalities in nine different genes (ABCC8, KCNJ11, GLUD1, GCK, HADH, SLC16A1, HNF4A, UCP2 and HNF1A) have been reported in HH, the most common being ABCC8 and KCNJ11. We describe the genetic aetiology and phenotype of Iranian patients with HH.MethodsRetrospective clinical, biochemical and genetic information was collected on 23 patients with biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
5
7
1
Order By: Relevance
“…Most of their patients had variants in the HADH gene and the ABCC8 gene was the next gene with frequent variants. e only similar variants between this study and the present one are the splicing variants in the ABCC8 gene (c.2041-21G > A) [16]. ey reported that their female heterozygous patient had died at the age of 3 months.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Most of their patients had variants in the HADH gene and the ABCC8 gene was the next gene with frequent variants. e only similar variants between this study and the present one are the splicing variants in the ABCC8 gene (c.2041-21G > A) [16]. ey reported that their female heterozygous patient had died at the age of 3 months.…”
Section: Discussionsupporting
confidence: 78%
“…In our studied population, only one compound heterozygous variant was found. Compound heterozygous status has been reported in other studies while Senniappan et al have previously reported the same heterozygous variants in the Iranian population [16,19]. eir patient was a female child who died at 3 months of age [16].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Complete knockout of channel activity was confirmed in isolated membrane patches of β-cells from homozygous mutant fish (see below), which we thus term SUR1 -/-. Infants with CHI often have macrosomia 28,29 , but, as with mouse knockouts 18,30,31 there was no significant difference in growth between SUR1 mutants and wild type (Fig. 1B).…”
Section: Genome-modified Zebrafish Model Of Sur1 Lofmentioning
confidence: 92%